Resolutions Adopted on Tax Matters By Local Self-Governments in Poland - Presnarowicz, Łukasz (Central European Academy Law Review, 2025)
Article 168 of the Constitution of the Republic of Poland of 2 April 1997 states: ‘Local government units have the right to determine the amount of local taxes and fees to the extent specified by law.’ This Article grants autonomy to local government units to legislate on the amount of local taxes and fees; however, the Article states that this can be done to the extent indicated in the laws. The laws that contain the issues in question are: Tax Ordinance, the Law on Local Taxes and Fees, the Law on Agricultural Taxes, and the Law on Forest Taxes. An analysis of the laws in question shows that in the current state of the law in Poland, only municipalities are granted certain powers in terms of establishing taxes, but they are not unlimited. Among other things, the tax independence of municipalities is expressed in these statutory powers.